A new species of Thalleulia Razowski, 2004 from Costa Rica with the first reported female of the genus (Lepidoptera: Tortricidae: Euliina) - Brown, John W. (Zootaxa, 2022)
The genus Thalleulia Razowski, 2004 was previously represented by three species known only from Ecuador, each described from a single male. A new species, Thalleulia bisexta, n. sp., is described and illustrated from Costa Rica, based on both sexes. Female genitalia indicate a close relationship between Thalleulia and Inape Razowski, 1988.